Based on the experience of physical rehabilitation of children with cerebral palsy using Bobat-therapy - Імас, Євгеній; Кашуба, Віталій; Буховець, Божена (Slobozhanskyi Herald of Science and Sport, 2018)
Yevgeny Imas, Vitaliy Kashuba & Bozhena Bukhovets Purpose: to determine the effectiveness of using Bobat-therapy in the program of physical rehabilitation of children with cerebral palsy. Material & Methods: theoretical analysis and generalization of literary and documentary sources; the use of diagnostic scales "Test cards of motor abilities of children", "Munich Functional Diagnostics", "The Gross Motor Function Classification System" and the method of mathematical data processing. Results: despite the presence of a large number of methods of physical rehabilitation of children with cerebral palsy, the problem of choosing the most effective one arose. As a result of modern scientific research of scientists from different countries, Bobat-therapy is found to be an effective method in the physical rehabilitation of children with cerebral palsy. However, there is a problem with the definition of criteria for differentiating the use of Bobat-therapy products, and also with the creation of an algorithm for their use, have not previously been investigated. Conclusion: according to the results of our scientific research, the program of physical rehabilitation of children with cerebral palsy using the Bobat-therapy method, taking into account the developed algorithm of differentiated use of Bobat-therapy, is effective, as evidenced by the data obtained. For example, the children of the OG noted the improvement of motor functions in the "The Gross Motor Function Classification System" system, the motor capabilities behind the "Test Card for Children’s Motor Capabilities" and the normalization of the psychophysical state behind the "Munich Functional Diagnostics".